Balancing innovation and cross-border consumer protection: a look at regulatory challenges for FinTech companies - Petruņko, Žaklīna (Riga Graduate School of Law, 2024)
The research offers a succinct synopsis of the obstacles faced by Fintech companies in Latvia, highlighting the paramount significance of proficient personnel and strong regulatory environments in guaranteeing their worldwide competitiveness. It explores the nuances of regulatory supervision, pointing out related dangers and arguing in favour of uniform regulatory frameworks to encourage the expansion of the Fintech industry. It also delves into the complex balancing act needed to maintain consumer protection, guarantee financial stability, and promote innovation in the EU Fintech scene. The abstract discusses ways to improve regulatory coherence, close consumer protection gaps, and support Fintech advancement. It also addresses access to international payment systems, fragmented rules, and the Fintech environment.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Consumer protection law; innovation; Fintech